2002
DOI: 10.1179/026708302225001769
|View full text |Cite
|
Sign up to set email alerts
|

Effects of addition of TiN nanoparticles on microstructure and mechanical properties of TiC based cermets

et al.

Abstract: Titanium carbide based cermets with additions of titanium nitride nanoparticles were fabricated by using ultrasonic dispersion and conventional powder metallurgy techniques. In order to characterise the microstructure, SEM and TEM have been utilised. The results show that the microstructure becomes ® ner with increasing additions of titanium nitride nanoparticles. The mechanical properties were also measured and the results show that the properties do not change monotonously with the amount of titanium nitride… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(7 citation statements)
references
References 2 publications
0
7
0
Order By: Relevance
“…Niihara [4] reported that mechanical properties of ceramics could be improved by addition of nano-powder. There are several papers on the microstructure and mechanical properties of Ti(C,N)-based cermets with partial addition of nano-TiN [5][6][7][8]. The results show that the properties of cermets are controlled by the dispersion of nano-TiN reinforcements in ceramic matrix to some extent.…”
Section: Introductionmentioning
confidence: 90%
“…Niihara [4] reported that mechanical properties of ceramics could be improved by addition of nano-powder. There are several papers on the microstructure and mechanical properties of Ti(C,N)-based cermets with partial addition of nano-TiN [5][6][7][8]. The results show that the properties of cermets are controlled by the dispersion of nano-TiN reinforcements in ceramic matrix to some extent.…”
Section: Introductionmentioning
confidence: 90%
“…In 1970s, TiN was introduced into TiC-Ni-Mo cermets [2]. In 1980s, Japanese scholar Niihara [3] reported that mechanical properties of ceramics could be improved after addition of nano-powders [4][5][6][7]. From then on, nano-TiN powder was partially added into Ti(C,N)-based cermets to improve the toughness.…”
Section: Introductionmentioning
confidence: 99%
“…At present, it has been attracting much attention from researchers because of their excellent wear resistance, good high temperature hardness, perfect chemical stability, very low friction coefficient to metals, superior thermal deformation resistance (Zackrisson et al, 2001;Liu et al, 2005;Liu et al, 2002;Lindahl et al, 1993;Andrén, 2001;Mari et al, 2003;Zackrisson et al, 1996;Ahn and Kang, 2001;Chao et al, 2005;Lindahl et al, 1999). Previous works have shown that by using nano-sized starting powders, the microstructure and the mechanical property of Ti(C,N)-based cermet can cause significant changes (Liu et al, 2002;Chao et al, 2005). Moreover, it was reported that nano-sized TiN addition is more effective than micro-sized TiN in improving the mechanical properties and the cutting performance of TiC-based cermets .…”
Section: Introductionmentioning
confidence: 99%